Duck TRIM32 Functions in IFN-β Signaling Against the Infection of H5N6 Highly Pathogenic Avian Influenza Virus - Wu, Siyu; Zhang, Junsheng; Xue, Qian; Liu, Jing; Huang, Bingzhong; He, Zhuoliang; Huang, Jianni; Zu, Shaopo; Chen, Zuxian; Zhao, Bingbing; Liao, Ming; Jiao, Peirong (Frontiers in Immunology, 2020)
In mammals, tripartite motif 32 (TRIM32) is essential for regulating host innate immune responses to viral infections. However, the antiviral effect of TRIM32 in birds has not been reported. Here, we cloned the full-length duck TRIM32 (duTRIM32) cDNA from total spleen RNA of Peking duck. DuTRIM32 consists of 682 amino acids and has 95.5% similarity in amino acid sequences with chicken TRIM32 and 84.9% similarity with human TRIM32, respectively. DuTRIM32 mRNA was found to be ubiquitously expressed in all tested tissues from healthy ducks. Overexpression of duTRIM32 significantly activated the IFN-β promoter and upregulated the mRNA levels of IFN-β, IRF7 and Mx, which indicates that duTRIM32 is involved in the type I IFN pathway. Furthermore, duTRIM32 was found to directly interact with duck STING (duSTING) and to contribute to the expression of IFN-β mediated by duSTING. The mRNA level of duTRIM32 was significantly upregulated in the lungs and spleens of H5N6 highly pathogenic avian influenza virus (HPAIV) infected ducks 3 days post-infection (DPI). Furthermore, overexpression of duTRIM32 could inhibit the replication of H5N6 HPAIV in duck embryo fibroblasts (DEFs). Therefore, these results indicate that duTRIM32 is involved in the type I IFN pathway and exhibit an antiviral effect against H5N6 HPAIV infection.